Injection Of air control of propeller performance - Zhibo Wang; Jinjing Gu (Engineering Applications of Computational Fluid Mechanics)
With the rise of bubble lubrication technology in transport ships, the interaction between propellers and bubble flow has become increasingly important. On the basis of solving the Reynolds averaged equation and the volume fraction equation, a numerical model of the propeller in a water air mixed fluid was established using the sliding mesh technique. Based on verifying the numerical calculation model of the semi-immersed propeller, uncertainty analysis was conducted on the KP505 propeller flow numerical model, and the open water performance of the propeller was calculated to be affected by the injection position and injection volume. A linear model was established to describe the relationship between the open water performance of the propeller at the axis and the injection rate. The performance surface model was used to describe the effect of the air injection position moving towards the blade tip on open water performance at different air injection rates. The strength and dissipation of the tip vortex and hub vortex of propeller are affected by the radial air injection position. Air injection at the axis causes the hub vortex to expand and connects the tip vortex to form a vortex ring in the far field. The air injection position moves towards the blade tip, and the vortex system at the blade tip accelerates and rapidly dissipates.